2013
DOI: 10.1186/1743-422x-10-121
|View full text |Cite
|
Sign up to set email alerts
|

Do viruses require the cytoskeleton?

Abstract: BackgroundIt is generally thought that viruses require the cytoskeleton during their replication cycle. However, recent experiments in our laboratory with rubella virus, a member of the family Togaviridae (genus rubivirus), revealed that replication proceeded in the presence of drugs that inhibit microtubules. This study was done to expand on this observation.FindingsThe replication of three diverse viruses, Sindbis virus (SINV; family Togaviridae family), vesicular stomatitis virus (VSV; family Rhabdoviridae)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…Furthermore, VSV transport to the cell surface is reported to be Research article MT-dependent (Das et al, 2006). However, a recent study found no effect of MT depolymerization on VSV and SINV replication (Matthews et al, 2013). Thus the role of MTs in VSV and SINV replication remains unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, VSV transport to the cell surface is reported to be Research article MT-dependent (Das et al, 2006). However, a recent study found no effect of MT depolymerization on VSV and SINV replication (Matthews et al, 2013). Thus the role of MTs in VSV and SINV replication remains unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have been inconsistent in describing the effect on virus release of drugs that disrupt the cytoskeleton (4,(23)(24)(25). One of the problems is that viral mRNAs require cytoskeletal function to be efficiently translated (13,26).…”
Section: Resultsmentioning
confidence: 99%
“…Cytoskeleton is important for maintenance of cell shape, cell motility and intracellular transport [21], and it is generally thought that viruses need cytoskeleton during infection [20]. Here the interaction of several cytoskeletonassociated proteins with BmNPV was determined, and they were actin, enolase (En) and phosphoglycerate kinase (PGK).…”
Section: Discussionmentioning
confidence: 99%